Konstruksi Sosial Mahasiswa Program Studi Pendidikan Fisika Dalam Mengintegrasikan Ilmu Sains dengan Ilmu Islam Kajian Teori Peter L Berger - Cahyaningsih, Esty; Sabarudin, Sabarudin; Winarti, Winarti; Sari, Umu Salumita (Studi Multidisipliner: Jurnal Kajian Keislaman, 2024)
This study aims to analyze how students in the Physics Education Study Program construct their understanding of integrating scientific and Islamic knowledge, based on Peter L. Berger's social construction theory. This study utilized a qualitative approach with a case study method. Data were collected through observations, interviews, and documentation. The data were then analyzed using the interactive model proposed by Miles, Huberman, and Saldana, which includes data condensation, data presentation, and conclusion drawing. The results indicate that the social construction among Physics Education students at UIN Sunan Kalijaga occurs through three processes: externalization, objectivation, and internalization. Externalization occurs when students express ideas, concepts, and opinions during academic discussions, particularly in courses focused on the integration of Islam and Science as well as in related religious studies within organizations. Objectivation happens when their ideas regarding the integration of Islamic knowledge and science gain acceptance during academic discussions, leading to a consensus that it is crucial for physics educators to integrate Islamic teachings with scientific knowledge. Internalization takes place when students develop a sense of awe, wonder, and gratitude for God's creation. They become accustomed to reading verses from the Quran and recognize that religious and Islamic knowledge are interconnected and complementary, rather than separate entities.